Peran dan Keterlibatan Komite Sekolah dalam Meningkatkan Mutu Pendidikan di SMA Tamansiswa Pematangsiantar - Leni Rosnani (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This study aims to analyze the role and involvement of school committees in improving the quality of education services. This agency acts as an advisory agency, supporting agency, controlling agency, mediator. The quality of education at SMA Tamansiswa Pematangsiantar can be said to be good, but it must continue to be improved. The optimization committee in this school has carried out its four roles. There is good coordination between the school committee and the school on a regular basis and its implementation has been organized with a clear structure. This research is a qualitative field using case study research. Sources of data were taken from the Principal, Deputy Principal, Teachers, Students, and Parents. Data collection techniques are observation, interviews, and documents.